The relative value relevance of cash flow accounting disclosures by South African Banks - Trehaeven, Jake (Department of Finance and Tax, 2017)
During recent decades, researchers have developed the value relevance method of accounting based research. Value relevance, at its core, attempts to describe the information usefulness of a disclosure figure in relation to the impact it has on the market values of a given stock. Much of the focus of this research, both internationally and locally, has been based on earnings or balance sheet disclosures with little attention being paid to other sections of disclosure. This study takes the use of value relevance methods one step further and analyses the information usefulness of operating cash flow disclosures of financial firms versus non-financial firms in a South African context. The study proceeds to explain and then test the presumption that the nature of the banking business model makes operating cash flow disclosures irrelevant; some interesting and somewhat counter-intuitive results are obtained.